Yield and yield components of rapeseed as influenced by nitrogen and sulphur fertilization - Rafiqul Islam; HMM Tariq Hossain; Md Fazlul Karim; Md Nazmul Haque (Journal of Oilseed Brassica, 2026)
Effect of nitrogen (N) and sulphur (S) on yield and yield components of rapeseed (BARI Sarisha-14) was studied atShere-Bangla Agricultural University Farm, Dhaka, Bangladesh during two consecutive Rabi seasons of 2014-15 and2015-16. The experiment was laid out in split-plot design with three replications, consisted four levels of nitrogen viz., 0(control), 60, 120, 180 kg ha-1; and four levels of sulphur i.e., 0 (control), 15, 30, 45 kg ha-1. Levels of N and S showedsignificant effect on yield and yield contributing characters of BARI Sarisha-14. Results showed that application of 120kg N ha-1 with 45 kg S ha-1 gave the maximum yield. Results also revealed that the highest plant height, number ofbranches plant-1, number of siliquae plant-1, siliqua length, number of seeds siliqua-1, 1000-seed weight, seed yield,stover yield, biological yield and harvest index were obtained from the combination of 120 kg N with 45 kg S ha-1.